Influence of leg geometry on the performance of Bismuth Telluride-based Thermoelectric Generator - Hasan, Md. Nazibul; Mohamed Ali, Mohamed Sultan (ELEKTRIKA- Journal of Electrical Engineering, 2021)
Thermoelectric generators have been widely used to transform heat into electrical energy. Over the last few decades, researchers have studied the impact of thermoelement height and cross-section area on the efficiency of thermoelectric generators. This paper investigates and analyzes the effect of various thermoelement leg geometries, including rectangular, trapezoidal, cylindrical and cone, for a bismuth telluride-based thermoelectric generator using finite element analysis. The influence of thermoelement leg height on achieving an optimized temperature gradient, producing open-circuit voltage, and achieving maximum output power is studied. Based on the analysis, the thermoelectric generator with the cone shaped leg provided optimal temperature gradient, the open-circuit voltage of 87.8 mV and a maximum power of ~270 mW at a leg height of 5 mm.